CHANGES IN BUDGET AND TAX LEGISLATION DURING THE QUARANTINE PERIOD: IMPACT ON THE FINANCIAL COMPETITIVENESS OF TERRITORIES - Goncharenko , M. (Theory and Practice of Public Administration, 2020)
The article is devoted to the systematization of threats to local budgets caused by changes in budget and tax legislation during the quarantine period, analysis of possible revenue losses, as well as the development of recommendations to minimize fiscal risks and prevent imbalances of local governments. The main changes that directly affected the revenue side of local budgets were related to the property tax, in particular its two components - the payment for land and the tax on real estate other than land. The possible impact of declining entrepreneurial activity and economic downturn during the quarantine period on the financial capacity of local governments is analyzed. Local governments are recommended to assess the potential consequences of the decision to reduce flat tax rates in terms of possible losses to the budget, but, at the same time, take into account the interests of local entrepreneurs and try to minimize the negative effects of restrictive measures. It was found that the reduction of intergovernmental transfers to local budgets will limit the ability of local governments to implement infrastructure projects. Measures to ensure the balancing of local budgets during the quarantine period are proposed, including increasing the rationality, efficiency and targeted nature of the use of budget funds, optimizing the network, staff and contingents of budget institutions, reducing non-priority expenditures and more. Due to the deterioration of macroeconomic indicators, declining economic activity of economic entities, reducing the volume of targeted transfers from the state budget and changes in tax legislation aimed at supporting business, the chances of meeting the planned revenue indicators are reduced. At the same time, the burden on local budgets is growing significantly, as local governments need additional funding for preventive and anti-epidemic measures, as well as financial support for health facilities during quarantine. In view of this, it is very important to prevent imbalances in local budgets through prudent budget planning, the most accurate forecasting of revenue losses, as well as austerity. Only a comprehensive and systematic approach to budget management will allow local governments to overcome the critical period with the least loss and ensure the health of the community.